A 24-hour ambulatory blood pressure monitoring system for preeclampsia management in antenatal care. (2019) - Musyoka, Faith Mueni; Thiga, Moses Mwangi; Muketha, Geoffrey Muchiri
Abstract: The burden of preeclampsia has been a major concern worldwide both in developed and developing countries, making its prevention and management a major concern. Although motherhood is a fulfilling experience in society, it is connected to ill-health in some women, leading to maternal morbidity and mortality. The United Nations' Sustainable Development Goal (SDG) 3 aims to reduce the global maternal mortality ratio to less than 70 per 100, 000 live births. These deaths are caused by among other things, the emergence of conditions such as preeclampsia during pregnancy. Therefore, this study sought to implement a 24-hour ambulatory blood pressure monitoring solution for preeclampsia management, using a smartwatch in conjunction with a mobile and cloud-based application. Upon blood pressure readings from the expectant mother, an alert is sent to the assigned caregiver in order to initiate quick action. The researchers adopted a rapid prototyping approach in the implementation of the 24-hour ambulatory blood pressure monitoring system. An experimental design was adopted in the study to evaluate whether the system functionalities performed as expected. The system, which was evaluated in the context of a sample of 30 expectant mothers from two level 5 hospitals in Kenya, has been able to read blood pressure from expectant mothers' smartwatches. The real-time data is then sent to the caregivers' smartphone, as well as an alert. The solution has shown great potential for actual adoption in healthcare systems in developing countries, given its simplicity and affordability.